The impact of major trauma network triage systems on patients with major burns. Issue 8 (December 2016) - Nizamoglu, Metin; O'Connor, Edmund Fitzgerald; Bache, Sarah; Theodorakopoulou, Evgenia; Sen, Sankhya; Sherren, Peter; Barnes, David; Dziewulski, Peter
Highlights: Impact of major trauma centres on major burn patient outcomes. No improvement in transfer times, outcomes or survival. Significantly longer distance travelled by patients. Abstract: Introduction: Trauma is a leading cause of death and disability worldwide. Patients presenting with severe trauma and burns benefit from specifically trained multidisciplinary teams. Regional trauma systems have shown improved outcomes for trauma patients. The aim of this study is to determine whether the development of major trauma systems have improved the management of patients with major burns. Methods: A retrospective study was performed over a four-year period reviewing all major burns in adults and children received at a regional burns centre in the UK before and after the implementation of the regional trauma systems and major trauma centres (MTC). Comparisons were drawn between three areas: (1) Patients presenting before the introduction of MTC and after the introduction of MTC. (2) Patients referred from MTC and non-MTC within the region, following the introduction of MTC. (3) Patients referred using the urban trauma protocol and the rural trauma protocol. Results: Following the introduction of regional trauma systems and major trauma centres (MTC), isolated burn patients seen at our regional burns centre did not show any significant improvement in transfer times, admission resuscitation parameters, organ dysfunction or survival when referred from a MTC compared to a non-MTC emergency department. There was also no significant difference in survival when comparing referrals from all hospitals pre and post establishment of the major trauma network. Conclusion: No significant outcome benefit was demonstrated for burns patients referred via MTCs compared to non-MTCs. We suggest further research is needed to ascertain whether burns patients benefit from prolonged transfer times to a MTC compared to those seen at their local hospitals prior to transfer to a regional burns unit for further specialist care.